Solid electrolyte material and battery
A solid electrolyte material with a close-packed structure and expanded lattice addresses the low conductivity and safety issues of existing materials, enabling high-performance, hydrogen sulfide-free all-solid-state batteries.
Patent Information
- Application Number
- JP2019563958
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-01-05
- Filing Date
- 2018-12-17
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2038-12-17
AI Technical Summary
Existing solid electrolyte materials do not achieve high lithium ion conductivity, and all-solid-state batteries using sulfide solid electrolytes can generate hazardous hydrogen sulfide when exposed to the atmosphere, compromising safety.
A solid electrolyte material composed of Li, M, and X, where X is Cl, Br, or I, with a sublattice of X atoms having a close-packed structure and an expanded lattice, enhancing lithium ion conductivity and preventing hydrogen sulfide generation.
The material achieves high lithium ion conductivity and enables safe, efficient operation of all-solid-state secondary batteries without hydrogen sulfide generation, with improved charge and discharge characteristics.
Smart Images

Figure 0007611524000015 
Figure 0007611524000016 
Figure 0007611524000017
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a solid electrolyte material and a battery. [Background technology]
[0002] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte.
[0003] In Non-Patent Document 1, Li 3 Y.C.L. 6 has been disclosed.
[0004] In Non-Patent Document 2, Li 3 YBr 6 has been disclosed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2011-129312 A [Non-patent literature]
[0006] [Non-Patent Document 1] Z.Anorg.Allg.Chem.623(1997), 1067-1073. [Non-Patent Document 2] Z.Anorg.Allg.Chem.623(1997), 1352-1356. Summary of the Invention [Problem to be solved by the invention]
[0007] In the prior art, it is desirable to realize a solid electrolyte material having high lithium ion conductivity. [Means for solving the problem]
[0008] A solid electrolyte material according to an embodiment of the present disclosure is composed of Li, M, and X. The M is at least one selected from metal elements, and the X is at least one selected from the group consisting of Cl, Br, and I. A sublattice of a plurality of the X atoms has a close-packed structure. The average value of the distance between two adjacent X atoms among the plurality of X atoms is 1.8% or more longer than the distance between two adjacent X atoms in a rock salt structure composed only of Li and the X. Effect of the Invention
[0009] According to the present disclosure, a solid electrolyte material having high lithium ion conductivity can be realized. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic configuration of a battery according to a third embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing a method for evaluating ionic conductivity. [Diagram 3] FIG. 3 is a graph showing the evaluation results of ionic conductivity by AC impedance measurement. [Figure 4A] FIG. 4A is a graph showing the XRD patterns for Examples A1-A11. [Figure 4B] FIG. 4B is a graph showing the XRD patterns for Examples A1-A11. [Diagram 5] FIG. 5 is a graph showing the initial discharge characteristics. [Figure 6A] FIG. 6A is a graph showing the XRD patterns for Examples B1-B13. [Figure 6B] FIG. 6B is a graph showing the XRD patterns for Examples B1-B13. [Figure 7A] FIG. 7A is a graph showing the XRD pattern in Comparative Example 1-3. [Figure 7B] FIG. 7B is a graph showing the XRD pattern in Comparative Example 1-3. [Figure 8]FIG. 8 is a graph showing the relationship between lithium ion conductivity and aave / aLiX in Examples A1 to A11, B1 to B13, and Comparative Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0012] (Embodiment 1) The solid electrolyte material in the first embodiment is a material made of Li and M which are cations, and X which is an anion.
[0013] M is at least one selected from metal elements.
[0014] X is at least one selected from the group consisting of Cl, Br, and I.
[0015] The sublattice of the plurality of X atoms contained in the solid electrolyte material in the first embodiment has a close-packed structure.
[0016] In the solid electrolyte material in the first embodiment, the average value of the distance between two adjacent X atoms among the plurality of X atoms is longer by 1.8% or more than the distance between two adjacent X atoms in a rock salt structure consisting of only Li and X.
[0017] According to the above-mentioned configuration, a halide solid electrolyte material, which is a solid electrolyte material having high lithium ion conductivity, can be realized.
[0018] Moreover, according to the above configuration, by using the solid electrolyte material of the first embodiment, an all-solid-state secondary battery having excellent charge / discharge characteristics can be realized.
[0019] Moreover, by using the solid electrolyte material of the first embodiment, an all-solid-state secondary battery that does not contain sulfur can be realized. That is, the solid electrolyte material of the first embodiment does not have a structure that generates hydrogen sulfide when exposed to the air (for example, the structure of Patent Document 1). Therefore, it is possible to realize an all-solid-state secondary battery that does not generate hydrogen sulfide and is excellent in safety.
[0020] In addition, the first conversion pattern obtained by converting the X-ray diffraction pattern of the solid electrolyte material in the first embodiment so that the horizontal axis is the diffraction angle 2θ to q is obtained when the value of q is 2.11 Å. -1 More than 2.31 Å -1 The range is equal to or less than the base peak.
[0021] Here, q = 4πsinθ / λ, where λ is the wavelength of the X-rays.
[0022] The X-ray diffraction pattern is plotted on the horizontal axis from the diffraction angle 2θ to q / q 2 The second conversion pattern is obtained by converting the q / q 2 Within a first range in which the value of q / q is 0.50 or more and 0.52 or less, 2 In a second range in which the value of q / q is 1.28 or more and 1.30 or less, 2 in a third range in which the value is 1.51 or more and 1.54 or less.
[0023] Here, q 2 is the value of q corresponding to the reference peak in the first transformation pattern.
[0024] According to the above configuration, a solid electrolyte material having high lithium ion conductivity can be realized.
[0025] The solid electrolyte material in the first embodiment is
number
[0026] According to the above configuration, a solid electrolyte material having high lithium ion conductivity can be realized.
[0027] Where:
number
[0028] q 1 is the value of q of the peak that falls within the first range.
[0029] q 2 is the above mentioned q 2 The value is
[0030] q 3 is the value of q of the peak that falls within the second range.
[0031] q 4 is the value of q of the peak that falls within the third range.
[0032] c 1 =2 / 3, c 2 =√(41 / 24), c 3 =√(17 / 6), c 4 = 2. However, if sufficient diffraction intensity is not obtained, in the second conversion pattern, q 1 From q 4 q of i If the peak corresponding to is not included in the above range, i =0.
[0033] That is, when the peak is included in the first range, 1 = 2 / 3, and if the peak is not included in the first range, c 1 =0.
[0034] Also, c 2 =√(41 / 24).
[0035] When the peak is included in the second range, 3 = √ (17 / 6), and if the peak is not included in the second range, c 3 =0.
[0036] When the peak is included in the third range, 4 = 2, and if the peak is not included in the third range, c 4 =0.
[0037] n is c i c ≠ 0 i For example, c i All are c i If ≠ 0, then n = 4.
[0038] In addition, a in formula (1) LiX teeth,
number
[0039] The molar ratio of Cl, Br, and I contained in X of the solid electrolyte material in the first embodiment is Cl:Br:I=x Cl :x Br :x I (However, x Cl +x Br +x I =1).
[0040] Also, a LiCl = 5.130 Å (= lattice constant of LiCl), a LiBr = 5.500 Å (= lattice constant of LiBr), a LiI = 6.0257 Å (= the lattice constant of LiI).
[0041] The solid electrolyte material in the first embodiment may include a first crystal phase. The first crystal phase may be a crystal phase that provides the above-mentioned characteristic diffraction pattern.
[0042] That is, the solid electrolyte material in the first embodiment may include a first crystal phase.
[0043] The first crystal phase, which gives rise to the above-mentioned characteristic diffraction pattern, indicates that the sublattice of the anions has a hexagonal close-packed structure, or a structure in which the atomic arrangement is a distorted hexagonal close-packed structure, and that the average distance between the anions is expanded by 1.8% or more compared to a rock salt crystal consisting of Li and a halogen. Normally, it was thought that high ionic conductivity would not be achieved when the anion exhibited a close-packed structure (Nature Materials 14, 1026-1031 (2015)). On the other hand, as a result of the inventors' investigation, it was found that when the anion has a hexagonal close-packed structure and satisfies the above-mentioned formula (1), a 1×10 -4 They found that it is possible to obtain high lithium ion conductivity of more than 1.5 S / cm. This is believed to be due to the fact that the expansion of the lattice promotes the migration from the octahedral sites, which is the rate-limiting process for ion conduction, to the metastable tetrahedral sites.
[0044] According to the above-mentioned configuration, a solid electrolyte material having higher lithium ion conductivity can be realized.
[0045] The first crystal phase from which the above-mentioned characteristic diffraction pattern can be obtained is not limited to a specific crystal structure, but examples thereof include the following crystal structures.
[0046] For example, Li, which has a crystal structure belonging to the space group P-3m1 3 ErCl 6 Lithium ion exchange (LEC) structure or a crystal structure belonging to the space group Pnma 3 YbCl 6 (hereinafter referred to as LYC) structure. Its detailed atomic arrangement is listed in the Inorganic Crystal Structure Database (ICSD) (LEC structure: ICSD No. 50151, LYC structure: ICSD No. 50152).
[0047] The solid electrolyte material in the first embodiment may include a heterogeneous crystal phase having a crystal structure different from that of the first crystal phase.
[0048] In addition, the above q 1 From q 4 When determining q, if there are nearby high intensity peaks, the weighted average of the peak positions and peak intensities of the nearby peaks is taken. 1 From q 4 For example, the nearest q 11 andq 12 The intensity at the position is I 11 and I 12 If a peak exists, q 1 =(q 11 I 11 +q 12 I 12 ) / (I 11 +I 12 ) as q 1 may be determined.
[0049] In this case, the symmetry of the crystal structure may be taken into consideration, and a weighted average of peaks that are equivalent when a virtual higher-order symmetry is taken into consideration. As a specific example, the above-mentioned LYC structure is an orthorhombic crystal structure, but if attention is paid only to the arrangement of anions, it can be considered to be a distorted hexagonal close-packed structure, as mentioned above. If the LYC structure is approximately considered to be a hexagonal close-packed structure, the (401) and (231) faces of the LYC structure are both approximately equivalent to the (101) face in the hexagonal close-packed structure. Therefore, when the diffraction peaks from the (401) and (231) faces can be separated, the weighted average weighted by the peak intensities of both faces can be used to obtain q x The value of may be calculated.
[0050] In the first crystal phase, the number of moles of cations among the constituent elements may be less than the number of moles of anions, thereby forming vacant sites for the conduction of lithium ions and improving ionic conductivity.
[0051] (Embodiment 2) Hereinafter, the second embodiment will be described. Descriptions that overlap with the first embodiment will be omitted as appropriate.
[0052] The solid electrolyte material in the second embodiment further includes the following components in addition to the components of the solid electrolyte material in the first embodiment described above.
[0053] The X-ray diffraction pattern of the solid electrolyte material in the second embodiment is converted so that the horizontal axis is the diffraction angle 2θ to q. The first conversion pattern has a value of q of 1.76 Å. -1 More than 2.18 Å -1 The range is equal to or less than the base peak.
[0054] Here, q = 4πsinθ / λ, where λ is the wavelength of the X-rays.
[0055] The X-ray diffraction pattern is plotted on the horizontal axis from the diffraction angle 2θ to q / q 1 The second conversion pattern is obtained by converting the q / q 1 Within a first range in which the value of q / q ' is 1.14 or more and 1.17 or less, 1 Within a second range in which the value of q / q ' is 1.62 or more and 1.65 or less, 1 Within a third range in which the value of q / q ' is 1.88 or more and 1.94 or less, 1 and a fourth range in which the value of ' is 1.9 or more and 2.1 or less.
[0056] Here, q 1 ' is the value of q corresponding to the reference peak in the first transformation pattern.
[0057] According to the above-mentioned configuration, a halide solid electrolyte material, which is a solid electrolyte material having high lithium ion conductivity, can be realized.
[0058] Moreover, according to the above configuration, by using the solid electrolyte material of the second embodiment, an all-solid-state secondary battery having excellent charge / discharge characteristics can be realized.
[0059] The solid electrolyte material in the second embodiment is
number
[0060] According to the above configuration, a solid electrolyte material having high lithium ion conductivity can be realized.
[0061] Where:
number
[0062] q 1 ' is the above mentioned q 1 ' value.
[0063] q 2 ' is the value of q of the peak that falls within the first range.
[0064] q 3 ' is the value of q of the peak that falls within the second range.
[0065] q 4 ' is the value of q of the peak that falls within the third range.
[0066] q 5 ' is the value of q of the peak that falls within the fourth range.
[0067] c 1 '=√3, c 2 '=2, c 3 '=2√2, c 4 '=√11, c 5 However, sufficient diffraction intensity is not obtained, and q 1 ' to q 5 'Some q i If the peak corresponding to ' does not fall within the above range, c i '=0.
[0068] That is, c 1 '=√3.
[0069] When the peak is included in the first range, 2 '=2, and if the peak is not included in the first range, c 2 '=0.
[0070] When the peak is included in the second range, 3 '=2√2, and when the peak is not included in the second range, c 3 '=0.
[0071] When the peak is included in the third range, 4 '=√11, and when the peak is not included in the third range, c 4 '=0.
[0072] When the peak is included in the fourth range, 5 '=√12, and when the peak is not included in the fourth range, c 5 '=0.
[0073] n' is c i ' ≠ 0 i ' is the number of '. For example, c i ' is all c i If '≠0, then n=5.
[0074] a LiX is the formula (3) described in the first embodiment above.
[0075] The solid electrolyte material in the second embodiment may include a second crystal phase. The second crystal phase may be a crystal phase that provides the above-mentioned characteristic diffraction pattern.
[0076] That is, the solid electrolyte material in the second embodiment may include a second crystal phase.
[0077] The second crystal phase, which gives rise to the above-mentioned characteristic diffraction pattern, indicates that the sublattice of the anion has a cubic close-packed structure, or a structure in which the atomic arrangement is a distorted cubic close-packed structure, and that the lattice constant corresponding to the rock-salt structure is expanded by 1.8% or more compared to a crystal of a rock-salt structure consisting of Li and a halogen. It was generally believed that high ionic conductivity would not be achieved when the anion exhibited a close-packed structure (Nature Materials 14, 1026-1031 (2015)). On the other hand, as a result of the inventors' investigation, it was found that when the anion has a cubic close-packed structure and satisfies the above-mentioned formula (1), a lattice constant of 1×10 -4 They found that it is possible to obtain high lithium ion conductivity of more than 1.5 S / cm. This is believed to be due to the fact that the expansion of the lattice promotes the migration from the octahedral sites, which is the rate-limiting process for ion conduction, to the metastable tetrahedral sites.
[0078] The first crystal phase from which the above-mentioned characteristic diffraction pattern can be obtained is not limited to a specific crystal structure, but examples thereof include the following crystal structures.
[0079] For example, one is Li, which has a crystal structure belonging to the space group C2 / m. 3 ErBr 6 (hereinafter also referred to as LEB) structure. Its detailed atomic arrangement is listed in the Inorganic Crystal Structure Database (ICSD) (ICSD No. 50182). Other examples include spinel structures belonging to space groups such as Fd-3m or Imma, and inverse spinel structures.
[0080] The solid electrolyte material in the second embodiment may include a heterogeneous crystal phase having a crystal structure different from that of the second crystal phase.
[0081] According to the above-mentioned configuration, a solid electrolyte material having higher lithium ion conductivity can be realized.
[0082] In addition, the above q 1 ' to q 5When determining q', if there are nearby high intensity peaks, the weighted average of the peak positions and peak intensities of the nearby peaks is taken to determine q 1 ' to q 5 For example, the adjacent q 11 ' and q 12 The strength at the position of I 11 ' and I 12 If a peak of q exists, 1 '=(q 11 'I 11 '+q 12 'I 12 ') / (I 11 '+I 12 ') as q 1 ' may be defined.
[0083] In this case, the symmetry of the crystal structure may be taken into consideration, and a weighted average of peaks that are equivalent when a virtual higher-order symmetry is taken into consideration. As a specific example, the above-mentioned LYB structure is a monoclinic crystal structure, but if attention is paid only to the arrangement of anions, it can be considered to be a structure in which the cubic close-packed structure is distorted, as mentioned above. If the LYB structure is approximately considered to be a rock salt structure, the (20-2) and (131) planes of the LYB structure are both approximately equivalent to the (200) plane in the rock salt structure. Therefore, when the diffraction peaks from the (20-2) and (131) planes can be separated, the weighted average weighted by the peak intensities of both planes can be used to obtain q x You may also find the value of '.
[0084] In the first crystal phase, the number of moles of cations among the constituent elements may be less than the number of moles of anions, thereby forming vacant sites for the conduction of lithium ions and improving ionic conductivity.
[0085] The shape of the solid electrolyte material in the first or second embodiment is not particularly limited, and may be, for example, needle-like, spherical, or elliptical. For example, the solid electrolyte material in the first or second embodiment may be particles. A plurality of particles may be laminated and then molded into a pellet or plate by pressure.
[0086] For example, when the solid electrolyte material in the first or second embodiment has a particulate shape (eg, spherical shape), the median diameter may be 0.1 μm or more and 100 μm or less.
[0087] In the first or second embodiment, the median diameter may be not less than 0.5 μm and not more than 10 μm.
[0088] According to the above-mentioned configuration, the ion conductivity can be further increased, and a better dispersion state can be formed between the solid electrolyte material and the active material in the first or second embodiment.
[0089] In the first or second embodiment, the solid electrolyte material may have a smaller median diameter than the active material.
[0090] According to the above-mentioned configuration, the solid electrolyte material and the active material in the first or second embodiment can be more favorably dispersed.
[0091] In this disclosure, the expression "a range in which a given value A is from value B to value C" means "a range in which B≦A≦C."
[0092] <Method of manufacturing solid electrolyte material> The solid electrolyte material in the first or second embodiment can be produced, for example, by the following method.
[0093] Prepare raw powder of binary halide to obtain the desired element. For example, Li 2.5 Y 0.5 Zr 0.5 Cl 6 When preparing a solid electrolyte material with the composition, LiCl and YCl 3 and ZrCl 4and are prepared in a molar ratio of 2.5:0.5:0.5. At this time, the composition of the anions can be determined by selecting the type of raw material powder. After thoroughly mixing the raw material powders, the raw material powders are mixed, crushed, and reacted with each other using a mechanochemical milling method. After that, the raw material powders may be sintered in a vacuum or in an inert atmosphere. Alternatively, the raw material powders may be sintered in a vacuum or in an inert atmosphere after thoroughly mixing the raw material powders. The sintering conditions may be, for example, within a range of 100°C to 650°C, and sintering may be performed for 1 hour or more.
[0094] As a result, a solid electrolyte material having the above-mentioned composition is obtained.
[0095] The composition of the crystalline phase in the solid material, the crystalline structure, and the positions of each peak in the X-ray diffraction pattern using Cu-Kα as a radiation source and the conversion pattern can be determined by adjusting the raw material ratio and the reaction method and reaction conditions of the raw material powders.
[0096] (Embodiment 3) Hereinafter, the third embodiment will be described. Descriptions that overlap with the first or second embodiment will be omitted as appropriate.
[0097] The battery in the third embodiment is constructed using the solid electrolyte material described in the first or second embodiment above.
[0098] The battery in the third embodiment includes a solid electrolyte material, a positive electrode, a negative electrode, and an electrolyte layer.
[0099] The electrolyte layer is a layer provided between the positive electrode and the negative electrode.
[0100] At least one of the positive electrode, the electrolyte layer, and the negative electrode includes the solid electrolyte material of the first or second embodiment.
[0101] According to the above configuration, the charge / discharge characteristics of the battery can be improved.
[0102] A specific example of the battery according to the third embodiment will be described below.
[0103] FIG. 1 is a cross-sectional view showing a schematic configuration of a battery 1000 according to the third embodiment.
[0104] The battery 1000 in the third embodiment includes a positive electrode 201 , a negative electrode 203 , and an electrolyte layer 202 .
[0105] The positive electrode 201 includes positive electrode active material particles 204 and solid electrolyte particles 100 .
[0106] The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203 .
[0107] The electrolyte layer 202 includes an electrolyte material (eg, a solid electrolyte material).
[0108] The negative electrode 203 includes negative electrode active material particles 205 and solid electrolyte particles 100 .
[0109] The solid electrolyte particle 100 is a particle made of the solid electrolyte material of the first or second embodiment, or a particle containing the solid electrolyte material of the first or second embodiment as a main component.
[0110] The positive electrode 201 includes a material having a property of absorbing and releasing metal ions (for example, lithium ions). The positive electrode 201 includes, for example, a positive electrode active material (for example, positive electrode active material particles 204).
[0111] The positive electrode active material may be, for example, a lithium-containing transition metal oxide (e.g., Li(NiCoAl)O 2 , LiCoO 2 , etc.), transition metal fluorides, polyanionic and fluorinated polyanionic materials, as well as transition metal sulfides, transition metal oxyfluorides, transition metal oxysulfides, transition metal oxynitrides, etc., may be used.
[0112] The median diameter of the positive electrode active material particles 204 may be 0.1 μm or more and 100 μm or less. If the median diameter of the positive electrode active material particles 204 is smaller than 0.1 μm, there is a possibility that the positive electrode active material particles 204 and the halide solid electrolyte material cannot form a good dispersion state in the positive electrode. As a result, the charge and discharge characteristics of the battery are deteriorated. Also, if the median diameter of the positive electrode active material particles 204 is larger than 100 μm, lithium diffusion in the positive electrode active material particles 204 is slowed down. For this reason, it may be difficult for the battery to operate at high power.
[0113] The median diameter of the positive electrode active material particles 204 may be larger than the median diameter of the halide solid electrolyte material, thereby forming a good dispersion state between the positive electrode active material particles 204 and the halide solid electrolyte material.
[0114] The volume ratio "v:100-v" of the positive electrode active material particles 204 and the halide solid electrolyte material contained in the positive electrode 201 may be 30≦v≦95. If v<30, it may be difficult to ensure a sufficient energy density of the battery. Also, if v>95, it may be difficult to operate at high output.
[0115] The thickness of the positive electrode 201 may be 10 μm or more and 500 μm or less. If the thickness of the positive electrode 201 is thinner than 10 μm, it may be difficult to ensure a sufficient energy density of the battery. If the thickness of the positive electrode 201 is thicker than 500 μm, it may be difficult to operate at high output.
[0116] The electrolyte layer 202 is a layer including an electrolyte material. The electrolyte material is, for example, a solid electrolyte material. That is, the electrolyte layer 202 may be a solid electrolyte layer.
[0117] The solid electrolyte layer may contain, as a main component, the solid electrolyte material according to the above-mentioned embodiment 1 or 2. That is, the solid electrolyte layer may contain, for example, 50% or more (50 wt % or more) of the solid electrolyte material according to the above-mentioned embodiment 1 or 2 in terms of weight ratio relative to the entire solid electrolyte layer.
[0118] According to the above configuration, the charge / discharge characteristics of the battery can be further improved.
[0119] The solid electrolyte layer may contain the solid electrolyte material according to the first or second embodiment described above in an amount of, for example, 70% or more by weight (70% by weight or more) relative to the entire solid electrolyte layer.
[0120] According to the above configuration, the charge / discharge characteristics of the battery can be further improved.
[0121] The solid electrolyte layer contains the solid electrolyte material of the first or second embodiment as a main component, and may further contain unavoidable impurities, or starting materials, by-products, and decomposition products used in synthesizing the solid electrolyte material.
[0122] The solid electrolyte layer may contain the solid electrolyte material of the first or second embodiment in a weight ratio of 100% (100 wt %) relative to the entire solid electrolyte layer, excluding unavoidable impurities.
[0123] According to the above configuration, the charge / discharge characteristics of the battery can be further improved.
[0124] As described above, the solid electrolyte layer may be composed of only the solid electrolyte material in the first or second embodiment.
[0125] Alternatively, the solid electrolyte may be made of only a solid electrolyte material different from the solid electrolyte material in the first or second embodiment. As the solid electrolyte material different from the solid electrolyte material in the first or second embodiment, for example, Li 2 MgX 4 , Li 2 FEX 4 , Li(Al,Ga,In)X 4 , Li 3 (Al,Ga,In)X 6, LiI, etc. (X: F, Cl, Br, I) can be used.
[0126] The solid electrolyte layer may simultaneously contain the solid electrolyte material of the first or second embodiment and a solid electrolyte material different from the solid electrolyte material of the first or second embodiment. In this case, both may be uniformly dispersed. A layer made of the solid electrolyte material of the first or second embodiment and a layer made of a solid electrolyte material different from the solid electrolyte material of the first or second embodiment may be arranged in order in the stacking direction of the battery.
[0127] The thickness of the solid electrolyte layer may be 1 μm or more and 1000 μm or less. If the thickness of the solid electrolyte layer is thinner than 1 μm, the possibility of short-circuiting between the positive electrode 201 and the negative electrode 203 increases. If the thickness of the solid electrolyte layer is thicker than 1000 μm, it may be difficult to operate at high output.
[0128] The negative electrode 203 includes a material having a property of absorbing and releasing metal ions (for example, lithium ions) The negative electrode 203 includes, for example, a negative electrode active material (for example, negative electrode active material particles 205).
[0129] For the negative electrode active material, metal materials, carbon materials, oxides, nitrides, tin compounds, silicon compounds, etc. can be used. The metal material may be a single metal. Alternatively, the metal material may be an alloy. Examples of metal materials include lithium metal and lithium alloys. Examples of carbon materials include natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite, amorphous carbon, etc. From the viewpoint of capacity density, silicon (Si), tin (Sn), silicon compounds, and tin compounds can be preferably used. When a negative electrode active material with a low average reaction voltage is used, the effect of suppressing electrolysis by the solid electrolyte material in the first or second embodiment is more effectively exhibited.
[0130] The median diameter of the negative electrode active material particles 205 may be 0.1 μm or more and 100 μm or less. If the median diameter of the negative electrode active material particles 205 is smaller than 0.1 μm, the negative electrode active material particles 205 and the solid electrolyte particles 100 may not form a good dispersion state in the negative electrode. This may result in a deterioration in the charge / discharge characteristics of the battery. If the median diameter of the negative electrode active material particles 205 is larger than 100 μm, the lithium diffusion in the negative electrode active material particles 205 becomes slow. This may result in a difficulty in operating the battery at high output.
[0131] The median diameter of the negative electrode active material particles 205 may be larger than the median diameter of the solid electrolyte particles 100. This allows the negative electrode active material particles 205 and the halide solid electrolyte material to be well dispersed.
[0132] The volume ratio "v:100-v" of the negative electrode active material particles 205 and the solid electrolyte particles 100 contained in the negative electrode 203 may be 30≦v≦95. If v<30, it may be difficult to ensure a sufficient energy density of the battery. Also, if v>95, it may be difficult to operate at high output.
[0133] The thickness of the negative electrode 203 may be 10 μm or more and 500 μm or less. If the thickness of the negative electrode is thinner than 10 μm, it may be difficult to ensure a sufficient energy density of the battery. Also, if the thickness of the negative electrode is thicker than 500 μm, it may be difficult to operate at high output.
[0134] At least one of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a sulfide solid electrolyte or an oxide solid electrolyte for the purpose of increasing ion conductivity or chemical stability / electrochemical stability. As the sulfide solid electrolyte, Li 2 SP 2 S 5 , Li 2 S-SiS 2 , Li 2 S.B. 2 S 3 , Li 2 S-GeS 2 , Li3.25 Ge 0.25 P 0.75 S 4 , Li 10 GeP 2 S 12 , etc. can be used. As an oxide solid electrolyte, LiTi 2 (PO 4 ) 3 and its element-substituted NASICON-type solid electrolyte, (LaLi)TiO 3 Perovskite-type solid electrolyte based on Li 14 ZnGe 4 O 16 , Li 4 SiO 4 , LiGeO 4 and its element-substituted LISICON-type solid electrolytes, Li 7 La 3 Zr 2 O 12 and its element-substituted garnet-type solid electrolytes, Li 3 N and its H-substituted derivatives, Li 3 PO 4 and N-substituted versions thereof, etc. may be used.
[0135] At least one of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain an organic polymer solid electrolyte for the purpose of increasing ion conductivity. For example, a compound of a polymer compound and a lithium salt may be used as the organic polymer solid electrolyte. The polymer compound may have an ethylene oxide structure. By having an ethylene oxide structure, a large amount of lithium salt can be contained, and the ion conductivity can be further increased. Examples of the lithium salt include LiPF 6 , LiBF 4 , LiSbF 6 , LiAsF 6 , LiSO 3 CF 3 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 C 2 F 5 ) 2 , LiN(SO2 CF 3 )(SO 2 C 4 F 9 ), LiC(SO 2 CF 3 ) 3 , etc. can be used. As the lithium salt, one type of lithium salt selected from these can be used alone. Alternatively, as the lithium salt, a mixture of two or more types of lithium salts selected from these can be used.
[0136] At least one of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a non-aqueous electrolyte solution, a gel electrolyte, or an ionic liquid for the purpose of facilitating the exchange of lithium ions and improving the output characteristics of the battery.
[0137] The non-aqueous electrolyte includes a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. As the non-aqueous solvent, a cyclic carbonate ester solvent, a chain carbonate ester solvent, a cyclic ether solvent, a chain ether solvent, a cyclic ester solvent, a chain ester solvent, a fluorine solvent, and the like can be used. Examples of the cyclic carbonate ester solvent include ethylene carbonate, propylene carbonate, butylene carbonate, and the like. Examples of the chain carbonate ester solvent include dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and the like. Examples of the cyclic ether solvent include tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, and the like. Examples of the chain ether solvent include 1,2-dimethoxyethane, 1,2-diethoxyethane, and the like. Examples of the cyclic ester solvent include γ-butyrolactone, and the like. Examples of the chain ester solvent include methyl acetate, and the like. Examples of fluorine solvents include fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, fluorodimethylene carbonate, and the like. As the non-aqueous solvent, one type of non-aqueous solvent selected from these can be used alone. Alternatively, as the non-aqueous solvent, a combination of two or more types of non-aqueous solvents selected from these can be used. The non-aqueous electrolyte may contain at least one type of fluorine solvent selected from the group consisting of fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, and fluorodimethylene carbonate. As the lithium salt, LiPF 6 , LiBF 4 , LiSbF 6 , LiAsF 6 , LiSO 3 CF 3 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 C 2 F 5 ) 2 , LiN(SO 2 CF 3 )(SO 2 C 4 F9 ), LiC(SO 2 CF 3 ) 3 , etc. can be used. As the lithium salt, one type of lithium salt selected from these can be used alone. Alternatively, as the lithium salt, a mixture of two or more types of lithium salts selected from these can be used. The concentration of the lithium salt is, for example, in the range of 0.5 to 2 mol / liter.
[0138] The gel electrolyte may be a polymer material containing a non-aqueous electrolyte solution, such as polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.
[0139] The cations constituting the ionic liquid may be aliphatic chain quaternary salts such as tetraalkylammonium and tetraalkylphosphonium, aliphatic cyclic ammoniums such as pyrrolidiniums, morpholiniums, imidazoliniums, tetrahydropyrimidiniums, piperaziniums, and piperidiniums, and nitrogen-containing heterocyclic aromatic cations such as pyridiniums and imidazoliums. The anions constituting the ionic liquid may be PF 6 - , B.F. 4 - , SbF 6- - , AsF 6 - , S.O. 3 CF 3 - , N(SO 2 CF 3 ) 2 - , N(SO 2 C 2 F 5 ) 2 - , N(SO 2 CF 3 )(SO 2 C 4 F 9 ) - , C(SO 2 CF3 ) 3 - The ionic liquid may contain a lithium salt.
[0140] At least one of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a binder for the purpose of improving adhesion between particles. The binder is used to improve the binding of the materials constituting the electrodes. Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polyacrylic acid methyl ester, polyacrylic acid ethyl ester, polyacrylic acid hexyl ester, polymethacrylic acid, polymethacrylic acid methyl ester, polymethacrylic acid ethyl ester, polymethacrylic acid hexyl ester, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene butadiene rubber, and carboxymethyl cellulose. The binder may be a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene. Two or more of these materials may be mixed and used as the binder.
[0141] At least one of the positive electrode 201 and the negative electrode 203 may contain a conductive assistant as necessary.
[0142] The conductive assistant is used to reduce the electrode resistance. Examples of the conductive assistant include graphites such as natural graphite or artificial graphite, carbon blacks such as acetylene black and ketjen black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride and aluminum, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, conductive polymer compounds such as polyaniline, polypyrrole, and polythiophene. The use of a carbon conductive assistant as the conductive assistant can reduce costs.
[0143] The battery in the second embodiment can be configured as batteries of various shapes, such as coin type, cylindrical type, square type, sheet type, button type, flat type, and laminated type. EXAMPLES
[0144] Hereinafter, the present disclosure will be described in detail using examples and comparative examples.
[0145] Example A1 [Preparation of solid electrolyte materials] In an argon atmosphere with a dew point of -60°C or less, raw material powders LiCl and YCl 3 and ZrCl 4 and LiCl:YCl in molar ratio 3 :ZrCl 4 The mixture was then weighed so that the ratio of the mixture to the total weight was 2.5:0.5:0.5. Thereafter, the mixture was milled at 600 rpm for 12 hours using a planetary ball mill.
[0146] [Evaluation of lithium ion conductivity] FIG. 2 is a schematic diagram showing a method for evaluating lithium ion conductivity.
[0147] The pressure molding die 300 is composed of a frame 301 made of electronically insulating polycarbonate, and an upper punch 303 and a lower punch 302 made of electronically conductive stainless steel.
[0148] Using the configuration shown in FIG. 2, the ionic conductivity was evaluated by the following method.
[0149] The powder of the solid electrolyte material of Example A1 was filled into a pressure molding die 300 in a dry atmosphere with a dew point of −30° C. or less, and uniaxially pressed at 400 MPa to prepare the conductivity measuring cell of Example A1.
[0150] While still in the pressurized state, conductors were routed from each of the upper punch 303 and the lower punch 302 and connected to a potentiostat (Princeton Applied Research, VersaSTAT4) equipped with a frequency response analyzer, and the ionic conductivity at room temperature was measured by electrochemical impedance measurement.
[0151] The Cole-Cole diagram of the impedance measurement results is shown in Figure 3.
[0152] In FIG. 3, the real value of the impedance at the measurement point (indicated by the arrow in FIG. 3) where the absolute value of the phase of the complex impedance is the smallest was regarded as the resistance value for ion conduction of the solid electrolyte of Example A1.
[0153] The ionic conductivity was calculated from the resistance value of the electrolyte according to the following formula. σ = (R SE ×S / t) -1 Here, σ is the ionic conductivity, S is the electrolyte area (the inner diameter of the frame mold 301 in FIG. 2), and R SE is the resistance value of the solid electrolyte in the impedance measurement, and t is the thickness of the electrolyte (the thickness of the compressed body of a plurality of solid electrolyte particles 100 in FIG. 2).
[0154] The ionic conductivity of the solid electrolyte material of Example A1 measured at 22° C. was 1.2×10 -3 S / cm.
[0155] [Crystal structure analysis] FIG. 4A is a graph showing the XRD pattern.
[0156] The results shown in FIG. 4A were determined by the following method.
[0157] That is, to analyze the crystal structure of the solid electrolyte, an X-ray diffraction pattern was measured using an X-ray diffractometer (RIGAKU MiniFlex600) in a dry environment with a dew point of -45° C. or less. Cu-Kα radiation was used as the X-ray source.
[0158] FIG. 4B shows the XRD pattern obtained by converting the horizontal axis 2θ of the XRD pattern described above into q=4πsin(θ) / λ, and further converting the q value at the peak position 2θ=31.64°, q 2 =2.222Å ―1 Normalized by q / q 2 In Fig. 4B, the q / q 2 Peaks were observed at positions q = 0.507, 1.289, and 1.530. The q values of these peaks were 1 / q 2 =0.507, q 3 / q 2 =1.289, q 4 / q 2 = 1.530, and using equation (2), ave The value of x in formula (3) was calculated to be 5.232 Å. Cl =1,x Br =0,x I =0 and a LiX Calculate a ave / a LiX Calculating the value of a ave / a LiX =1.020.
[0159] [Preparation of secondary battery] In an argon glove box, the solid electrolyte material of Example A1 and the active material LiCoO 2 The above were weighed out in a volume ratio of 70:30. These were mixed in an agate mortar to prepare a mixture.
[0160] In an insulating outer cylinder, the solid electrolyte material of Example A1 was laminated in the order of 700 μm thick, 8.5 mg of the above-mentioned mixture, and 16.5 mg of Al powder. This was then pressurized and molded at a pressure of 300 MPa to obtain a first electrode and a solid electrolyte layer.
[0161] Next, metal In (thickness: 200 μm) was laminated on the side of the solid electrolyte layer opposite to the side in contact with the first electrode, and this was pressurized and molded at a pressure of 80 MPa to produce a laminate consisting of the first electrode, the solid electrolyte layer, and the second electrode.
[0162] Next, stainless steel current collectors were placed on the top and bottom of the laminate, and current collecting leads were attached to the current collectors.
[0163] Finally, an insulating ferrule was used to isolate and seal the inside of the insulating outer cylinder from the outside atmosphere.
[0164] In this manner, a secondary battery of Example A1 was produced.
[0165] [Charge / discharge test] A charge / discharge test of the secondary battery of Example A1 was carried out in the following manner.
[0166] The secondary battery of Example A1 was placed in a thermostatic chamber at 25°C.
[0167] The battery was charged at a constant current at a current value corresponding to a 0.05C rate (20 hour rate) relative to the theoretical capacity of the battery, and charging was terminated at a voltage of 3.6V.
[0168] Next, the battery was discharged at a current value similarly resulting in a 0.05C rate, and the discharge was terminated at a voltage of 1.9V.
[0169] As a result of the above measurements, the initial discharge capacity of the secondary battery of Example A1 was 0.467 mAh.
[0170] Examples A2 to A11 The synthesis and evaluation methods of Examples A2 to A11 are described below.
[0171] [Preparation of solid electrolyte materials] In Examples A2 to A11, raw material powder was weighed to obtain a predetermined composition in a glove box maintained in a dry, low-oxygen atmosphere with a dew point of -60°C or less and an oxygen value of 5 ppm or less. The composition of the solid electrolyte prepared in each of Examples A2 to A11 is shown in Table 1 below. For example, when the composition is Li a Y b M c Cl d In the case of LiCl:YCl 3 :MCl m The materials were weighed and mixed in a ratio of a:b:c. Here, M is a metal element, and m is the valence of M. Then, the material was milled at 600 rpm for 12 hours using a planetary ball mill. In Examples A3 and A8, heat treatment was performed at 500°C and 300°C for 5 hours, respectively.
[0172] [Evaluation of ionic conductivity] Conductivity measurement cells for each of Examples A2 to A11 were prepared in a glove box maintained in a dry, low-oxygen atmosphere with a dew point of -90°C or less and an oxygen value of 5 ppm or less, in the same manner as in Example A1 above.
[0173] Other than this, the ionic conductivity was measured in the same manner as in Example A1 above.
[0174] The ionic conductivities in the above-mentioned Examples A2 to A11 are shown in Table 1 below.
[0175] [Crystal structure analysis] The crystal structure of each of the solid electrolyte materials of Examples A2 to A11 was measured in the same manner as in Example A1.
[0176] The X-ray diffraction patterns of Examples A1 to A11 are shown in FIG. 4A.
[0177] As in Example A1, the horizontal axis 2θ of the X-ray diffraction pattern shown in FIG. 4A was converted into q=4πsin(θ) / λ, and further, q=2.11 Å. -1 from 2.31 Å -1 The q value of the peak with high intensity in the range of q 2 When this is done, q2 Normalized by q / q 2 The diffraction pattern when the value of is plotted on the horizontal axis is shown in FIG. 4B.
[0178] q / q 2 Peaks were observed in the ranges of 0.50 to 0.52, 1.28 to 1.30, and 1.51 to 1.54, respectively. 2 The value of and q 2 The values of are shown in Table 1 below. Using these values and equation (2), ave Calculate the value of and use equation (3) to find ave / a LiX The calculated values are shown in Table 1 below.
[0179] However, for Example A3, q 1 ,q 2 ,q 3 ,q 4 In calculating either of these, the weighted average was calculated based on the intensity of the adjacent peaks. 1 The calculation of is the weighted average of the peaks q = 1.117 and 1.122, q 2 The calculation of is the weighted average of the peaks q = 2.195 and 2.202, q 3 The calculation of is the weighted average of the peaks q = 2.838 and 2.844, q 4 The weighted average value of the peaks at q = 3.355 and 3.369 was used to calculate.
[0180] [Preparation of secondary battery] In a glove box maintained at a dry, low-oxygen atmosphere with a dew point of -90°C or less and an oxygen value of 5 ppm or less, the solid electrolyte materials of Examples A2 to A11 and the positive electrode active material LiCoO 2 These were weighed out in a volume ratio of 30:70. These were mixed in an agate mortar to prepare the positive electrode mixtures of Examples A2 to A11.
[0181] Other than these, the secondary batteries of Examples A2 to A11 were each produced in the same manner as in Example A1.
[0182] [Charge / discharge test] The charge and discharge tests of the secondary batteries of Examples A2 to A11 were carried out in the same manner as in Example A1. The initial discharge characteristics of Examples A2 to A11 were similar to those of Example A1, and good discharge characteristics were obtained. The initial discharge characteristics of Example A2 are shown in FIG. 5. The discharge capacity of Example A2 was 0.657mAh.
[0183] Examples B1 to B13 The synthesis and evaluation methods of Examples B1 to B13 are described below.
[0184] [Preparation of solid electrolyte materials] In Examples B1 to B13, the raw material powder was weighed in a glove box maintained in a dry, low-oxygen atmosphere with a dew point of -60°C or less and an oxygen value of 5 ppm or less. The compositions of the solid electrolytes produced in each of Examples B1 to B13 are shown in Table 2 below.
[0185] For example, the composition is Li a Y b M c Br d In the case of LiBr:YBr 3 :MBr m The mixture was weighed and mixed in a ratio of a:b:c. Here, M is a metal element, and m is the valence of M. Then, the mixture was milled at 600 rpm for 12 hours using a planetary ball mill. In Example B8, the mixture was then heat-treated at 300°C for 5 hours.
[0186] Except for the above, the solid electrolyte materials of Examples B1 to B13 were each produced in the same manner as in Example A1.
[0187] [Crystal structure analysis] The crystal structure of each of the solid electrolyte materials of Examples B1 to B13 was measured in the same manner as in Example A1 above.
[0188] The X-ray diffraction patterns of Examples B1 to B13 are shown in FIG. 6A.
[0189] The horizontal axis 2θ of the X-ray diffraction pattern shown in FIG. 6A is converted into q=4πsin(θ) / λ, and further, q=1.76Å. -1 ~2.18Å -1 The q value of the peak with high intensity in the range of q 1 ', q 1 ' normalized by q / q 1 The diffraction pattern when the value of ' is taken on the horizontal axis is shown in Figure 6B.
[0190] q / q 1 Peaks were observed in the ranges of ' from 1.14 to 1.17, 1.62 to 1.65, 1.88 to 1.94, and 1.9 to 2.1, respectively. 1 ' and the value of q 1 The values of a' are shown in Table 2 below. Using these values and equation (4), a ave Calculate the value of and use equation (3) to find ave / a LiX The calculated results are shown in Table 2 below.
[0191] [Evaluation of ionic conductivity] Conductivity measurement cells for each of Examples B1 to B13 were prepared in a glove box maintained in a dry, low-oxygen atmosphere with a dew point of -90°C or less and an oxygen value of 5 ppm or less, in the same manner as in Example A1 above.
[0192] Other than this, the ionic conductivity was measured in the same manner as in Example A1 above.
[0193] The ionic conductivities in the above-mentioned Examples B1 to B13 are shown in Table 2 below.
[0194] [Preparation of secondary battery] In a glove box maintained at a dry, low-oxygen atmosphere with a dew point of -90°C or less and an oxygen value of 5 ppm or less, the solid electrolyte materials of Examples B1 to B13 and the positive electrode active material LiCoO 2 These were weighed out in a volume ratio of 30:70. These were mixed in an agate mortar to prepare the positive electrode mixtures of Examples B1 to B13.
[0195] Other than these, the secondary batteries of Examples B1 to B13 were fabricated in the same manner as in Example A1 above.
[0196] [Charge / discharge test] A charge / discharge test was carried out on each of the secondary batteries of Examples B1 to B13 in the same manner as in Example A1. The initial discharge characteristics of Examples B1 to B13 were similar to those of Example A1, and good charge / discharge characteristics were obtained.
[0197] <Comparative Examples 1 to 3> The synthesis and evaluation methods of Comparative Examples 1 to 3 will be described below.
[0198] [Preparation of solid electrolyte materials] In Comparative Examples 1 to 3, the raw material powder was weighed in a glove box maintained in a dry, low-oxygen atmosphere with a dew point of -60°C or less and an oxygen value of 5 ppm or less. The compositions of the solid electrolytes produced in each of Comparative Examples 1 to 3 are shown in Table 3 below. In Comparative Example 3, a heat treatment was then performed at 200°C for 1 hour.
[0199] Except for the above, the solid electrolyte materials of Comparative Examples 1 to 3 were each produced in the same manner as in Example A1.
[0200] [Crystal structure analysis] The crystal structure of each of the solid electrolyte materials of Comparative Examples 1 to 3 was measured in the same manner as in Example A1.
[0201] The X-ray diffraction patterns of Comparative Examples 1 to 3 are shown in FIG. 7A.
[0202] As in Example B1, the horizontal axis 2θ of the X-ray diffraction pattern shown in FIG. 7A was converted into q=4πsin(θ) / λ, and further, q=1.76 Å. -1 from 2.18 Å -1 The q value of the peak with high intensity in the range of q 1 ', q 1 ' normalized by q / q 1The diffraction pattern when the value of ' is taken on the horizontal axis is shown in Figure 7B.
[0203] q / q 1 Peaks were observed in the ranges of ' from 1.14 to 1.17, 1.62 to 1.65, 1.88 to 1.94, and 1.9 to 2.1, respectively. 1 ' and the value of q 1 The values of a' are shown in Table 2 below. Using these values and equation (4), a ave Calculate the value of and use equation (3) to find ave / a LiX The calculated results are shown in Table 3 below.
[0204] However, for Comparative Example 3, q 1 ' and q 3 When calculating q', the weighted average was calculated based on the intensity of adjacent peaks. 1 ' is calculated using the weighted average of the peaks q=2.078 and 2.109, q 3 The weighted average value of the peaks at q=3.389 and 3.429 was used to calculate '.
[0205] [Evaluation of ionic conductivity] Conductivity measurement cells for each of Comparative Examples 1 to 3 were prepared in a glove box maintained in a dry, low-oxygen atmosphere with a dew point of -90°C or less and an oxygen value of 5 ppm or less, in the same manner as in Example A1 above.
[0206] Other than this, the ionic conductivity was measured in the same manner as in Example A1 above.
[0207] The ionic conductivities in the above-mentioned Comparative Examples 1 to 3 are shown in Table 3 below.
[0208] [Preparation of secondary battery] In a glove box maintained at a dry, low-oxygen atmosphere with a dew point of -90°C or less and an oxygen value of 5 ppm or less, the solid electrolyte materials of Comparative Example 2 and the positive electrode active material LiCoO 2These were weighed out in a volume ratio of 30:70. These were mixed in an agate mortar to prepare a positive electrode mixture of Comparative Example 2.
[0209] Other than these, the secondary battery of Comparative Example 2 was produced in the same manner as in Example A1.
[0210] [Charge / discharge test] In the same manner as in Example A1, a charge / discharge test was carried out on the secondary battery of Comparative Example 2. The initial discharge characteristics of Comparative Example 2 showed that the battery hardly discharged and did not operate as a battery.
[0211] The compositions and evaluation results of the above-mentioned Examples A1 to A11, B1 to B13 and Comparative Examples 1 to 3 are shown in Tables 1 to 3.
[0212] [Table 1]
[0213] [Table 2]
[0214] [Table 3]
[0215] ≪Consideration≫ In Examples A1 to A11 and B1 to B13, the heat resistance was 1×10 -4 It can be seen that it exhibits high ionic conductivity of more than S / cm.
[0216] In addition, in Examples A1 to A11, q / q 2Peaks were observed in the ranges of 0.50 to 0.52, 1.28 to 1.30, and 1.51 to 1.54 for the value of a / q', which are characteristic peaks observed when the sublattice consisting of halogen ions has a hexagonal close-packed structure or a structure in which the hexagonal close-packed structure is distorted. In Examples B1 to B13, peaks were observed in the ranges of 1.14-1.17, 1.625-1.645, 1.88-1.94, and 1.90-2.10 for the value of a / q', which are characteristic peaks observed when the sublattice consisting of halogen ions has a cubic close-packed structure or a structure in which the cubic close-packed structure is distorted. In Examples A1 to A11 and B1 to B13, ave / a LiX The value of was 1.018 or more. This corresponds to a lattice expansion of about 1.8% or more compared to the crystal structure consisting of only lithium and halogen having the same halogen ratio as each of the compositions of Examples A1 to A11 and B1 to B13. ave / a LiX The ionic conductivity and a value obtained in the present invention were less than 1.018. ave / a LiX The relationship between is shown in Figure 8. ave / a LiX In the region where is 1.018 or more, the ionic conductivity is 1×10 -4 It was found that excellent properties of more than S / cm could be obtained.
[0217] In particular, when comparing Example A1 and Comparative Example 3, although the constituent elements are the same, a ave / a LiX By providing a structure in which the value exceeded 1.018, the ionic conductivity was significantly improved compared to Comparative Example 3.
[0218] In addition, in Examples A1 to A11 and B1 to B13, all of the batteries showed charge and discharge operation at room temperature. On the other hand, in Comparative Example 2, almost no discharge capacity was obtained, and battery operation could not be confirmed. Furthermore, since the materials in Examples A1 to A1 and B1 to B13 do not contain sulfur as a constituent element, no hydrogen sulfide is generated.
[0219] From the above, it is demonstrated that the solid electrolyte material according to the present disclosure is an electrolyte material that does not generate hydrogen sulfide, exhibits high lithium ion conductivity, and is capable of performing good charge and discharge operations. [Industrial Applicability]
[0220] The battery of the present disclosure can be used, for example, as an all-solid-state lithium secondary battery. [Explanation of symbols]
[0221] 100 solid electrolyte particles 201 Positive electrode 202 Electrolyte layer 203 Negative electrode 204 Positive electrode active material particles 205 Negative electrode active material particles 300 Pressure molding die 301 Frame type 302 Punch bottom 303 Punch top 1000 batteries
Claims
1. Li, M and X, The M is at least one selected from metal elements, and includes Y; X is at least one selected from the group consisting of Cl, Br, and I; Li 3 M.X. 6 Based on A sublattice of a plurality of X atoms has a close-packed structure, Among the plurality of X atoms, the average value of the distance between two adjacent X atoms is 1.8% or more longer than the distance between two adjacent X atoms in a rock salt structure consisting only of Li and the X; Solid electrolyte material.
2. A first conversion pattern obtained by converting the X-ray diffraction pattern of the solid electrolyte material so that the horizontal axis is a diffraction angle q from 2θ, The value of q is 2.11 Å. -1 More than 2.31 Å -1 The first peak due to diffraction is within the range below, Here, q = 4π sin θ / λ, where λ is the wavelength of the X-rays. The X-ray diffraction pattern is a function of the diffraction angle 2θ to q / q 2 The second conversion pattern is obtained by converting the The q / q 2 Within a first range in which the value of q / q is 0.50 or more and 0.52 or less, 2 In a second range in which the value of q / q is 1.28 or more and 1.30 or less, 2 A third range in which the value is 1.51 or more and 1.54 or less, and at least one peak derived from diffraction is included, Here, q 2 is the value of q corresponding to the first peak in the first transformation pattern, The solid electrolyte material according to claim 1 .
3. In the second conversion pattern, When the peak is included in the first range, 1 = 2 / 3, when the peak due to the diffraction is not included in the first range, c 1 = 0, c 2 =√(41 / 24), When the peak is included in the second range, 3 = √(17 / 6), and when the peak due to the diffraction is not included in the second range, c 3 = 0, When the peak due to diffraction is included in the third range, 4 = 2, when the peak due to the diffraction is not included in the third range, c 4 = 0, The value of q of the diffraction-derived peak included in the first range is q 1 year, The value of q of the diffraction peak included in the second range is q 3 year, The value of q of the diffraction-derived peak included in the third range is q 4 year, [0010] year, Here, n is c i c that satisfies ≠ 0 i is the number of The molar ratio of Cl, Br, and I contained in X is Cl:Br:I=x Cl :x Br :x I year, Here, x Cl +x Br +x I = 1, a LiCl =5.130Å、a LiBr =5.500Å、a LiI =6.0257Å year, [0025] Then, [0030] That is, The solid electrolyte material according to claim 2 .
4. A first conversion pattern obtained by converting the X-ray diffraction pattern of the solid electrolyte material so that the horizontal axis is a diffraction angle q from 2θ, The value of q is 1.76 Å. -1 More than 2.18 Å -1 The first peak due to diffraction is within the range below, Here, q = 4π sin θ / λ, where λ is the wavelength of the X-rays. The X-ray diffraction pattern is a function of the diffraction angle 2θ to q / q 1 ', the second conversion pattern is obtained by converting The q / q 1 Within a first range in which the value of q / q′ is 1.14 or more and 1.17 or less, 1 Within a second range in which the value of q / q′ is 1.62 or more and 1.65 or less, 1 Within a third range in which the value of q / q′ is 1.88 or more and 1.94 or less, 1 A fourth range in which the value of ' is 1.9 or more and 2.1 or less, and at least one selected from the group consisting of a diffraction-derived peak, Here, q 1 ' is the value of q corresponding to the first peak in the first transformation pattern; The solid electrolyte material according to claim 1 .
5. In the second conversion pattern, c 1 ' = √3, When the peak due to diffraction is included in the first range, 2 '=2, when the peak due to the diffraction is not included in the first range, c 2 '=0, When the peak due to diffraction is included in the second range, 3 '=2√2, and when the peak due to the diffraction is not included in the second range, c 3 '=0, When the peak due to diffraction is included in the third range, 4 '=√11, and when the peak due to the diffraction is not included in the third range, c 4 '=0, When the peak due to diffraction is included in the fourth range, 5 '=√12, and when the peak due to the diffraction is not included in the fourth range, c 5 '=0, The value of q of the diffraction-derived peak included in the first range is q 2 'year, The value of q of the diffraction peak included in the second range is q 3 'year, The value of q of the diffraction peak included in the second range is q 4 'year, The value of q of the diffraction-derived peak included in the fourth range is q 5 'year, [0045] year, Here, n' is c i ' ≠ 0 i ' is the number of The molar ratio of Cl, Br, and I contained in X is Cl:Br:I=x Cl :x Br :x I year, Here, x Cl +x Br +x I = 1, a LiCl =5.130Å、a LiBr =5.500Å、a LiI =6.0257Å year, [0025] Then, [0030] That is, The solid electrolyte material according to claim 4.
6. The M further includes at least one selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, La, Al, Sm, Bi, Zr, Hf, Nb, and Ta; The solid electrolyte material according to claim 1 .
7. Composition formula Li a1 M a2 X a3 It is expressed as (a1+a2) / a3<0.7 is satisfied. The solid electrolyte material according to claim 1 .
8. A positive electrode and A negative electrode; an electrolyte layer provided between the positive electrode and the negative electrode; Equipped with At least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte layer comprises the solid electrolyte material according to any one of claims 1 to 7. battery.
Citation Information
Patent Citations
Method of manufacturing sulfide solid electrolyte material, sulfide solid electrolyte material, and lithium battery
JP2011129312A